An Intersectional Examination of the Portrayal of Native American Women in Wisconsin Museum Exhibits - (:unkn) unknown (My University, 2017)
This project examines how White curators at four museums in Wisconsin portray Native American women based on a number of institutional and individual curatorial choices. Intersectional Theory is used to explore how museums and museum professionals navigate questions of representation of a traditionally marginalized group. It places specific emphasis on the relationship between Community Curation and Intersectional Theory and explores whether or not the involvement of Native groups noticeably impacts representation of Native American women. The study examines the exhibits of four museums: The Abel Public Museum, The New Canton College of Anthropology, The Pineville Public Museum, and The Wisconsin Museum of Natural History. These institutions vary in size, scope, audience, and curatorial strategies. However, they all have exhibits that depict Native Americans. Museum professionals from each institution were also interviewed to better understand how individual embodiments of particular Intersections of identity do or do not impact curatorial philosophies. In addition, the questions of bias, authority, and perspective are also evaluated in conjunction with critical approaches to museology. Finally, it explores some of the ways in which these structures uphold existing frameworks of colonialism and White supremacy and how Intersectional museum exhibits can be developed to combat these paradigms and ensure more diverse and accurate representation.
Keywords: Exhibits; Intersectionality; Intersectional Theory; Museums; Native Americans; Women